Singapore : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Singapore. (IMF Staff Country Reports; Country Report ;, 2008)
This 2008 Article IV Consultation highlights that spillovers from the global slowdown and lingering turbulence in international financial markets have been propagated to Singapore mostly through the trade channel. Inflation has risen significantly on the back of international and home-grown cost pressures. Increases in food and energy prices have added to pressures from a hike in indirect takes, a housing boom, and tighter labor markets. Executive Directors have welcomed the recent steps by the Monetary Authority of Singapore to tighten the monetary policy stance further by adjusting the exchange rate target band.